Uprooting the diaspora : Jewish belonging and the "ethnic revolution" in Poland and Czechoslovakia, 1936-1946 - Cramsey, Sarah A. (Modern Jewish experience (Bloomington, Ind.), 2023)
"In Uprooting the Diaspora, Sarah Cramsey explores how the Jewish citizens rooted in interwar Poland and Czechoslovakia became the ideal citizenry for a post-World War II Jewish state in the Middle East. She asks, how did new interpretations of Jewish belonging emerge and gain support amongst Jewish and non-Jewish decision makers exiled from wartime east central Europe and the powerbrokers surrounding them? Usually, the creation of the State of Israel is cast as a story that begins with Herzl and is brought to fulfillment by the Holocaust. To reframe this trajectory, Cramsey draws on a vast array of historical sources to examine what she calls a "transnational conversation" carried out by a small but influential coterie of Allied statesmen, diplomats in international organizations, and Jewish leaders who decided that the overall disentangling of populations in postwar east central Europe demanded the simultaneous intellectual and logistical embrace of a Jewish homeland in Palestine as a territorial nationalist project. Uprooting the Diaspora slows down the chronology between 1936 and 1946 to show how individuals once invested in multi-ethnic visions of diasporic Jewishness within east central Europe came to define Jewishness primarily in ethnic terms. This revolution in thinking about Jewish belonging combined with a sweeping change in international norms related to population transfers and accelerated, deliberate postwar work on the ground in the region to further uproot Czechoslovak and Polish Jews from their prewar homes"--